2014
DOI: 10.1371/journal.pone.0108014
|View full text |Cite
|
Sign up to set email alerts
|

Induction of M2 Polarization in Primary Culture Liver Macrophages from Rats with Acute Pancreatitis

Abstract: Background and AimsSystemic inflammatory response syndrome (SIRS), a major process of severe acute pancreatitis (SAP), usually occurs after various activated proinflammatory cytokines, which are produced by macrophages such as liver macrophages. Macrophages can secrete not only proinflammatory mediators but also inhibitory inflammatory cytokines such as IL-10, leading to two different functional states defined as “polarization”. The main purpose of this study was to demonstrate the polarization of liver macrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 28 publications
2
12
0
1
Order By: Relevance
“…More importantly, the levels of plasma CRP were positively correlated with the numbers of CD14+CD163- and CD14+CD163-MAC387+ M1 monocytes in the MAP patients. These data were consistent with a previous report of M1-polarized macrophages at the early stage in rats with AP[ 29 ]. Similarly, our previous study had found that peripheral blood polarized M1 monocytes are present in patients with tuberculous pleural effusion (TPE)[ 15 ].…”
Section: Discussionsupporting
confidence: 94%
“…More importantly, the levels of plasma CRP were positively correlated with the numbers of CD14+CD163- and CD14+CD163-MAC387+ M1 monocytes in the MAP patients. These data were consistent with a previous report of M1-polarized macrophages at the early stage in rats with AP[ 29 ]. Similarly, our previous study had found that peripheral blood polarized M1 monocytes are present in patients with tuberculous pleural effusion (TPE)[ 15 ].…”
Section: Discussionsupporting
confidence: 94%
“…The M1 state was confirmed by the up-regulated expression of M1 phenotypes and down-regulated expression of M2 phenotypes. And the results conform to the conventional theory that macrophages can induce pro-inflammatory cytokines and amplify the degree of the inflammation during early phase of SAP[31,32]. …”
Section: Discussionsupporting
confidence: 85%
“…Thus, in models of alcoholic and nonalcoholic liver disease, M2-polarized Kupffer cells induced apoptosis of Kupffer cells with an M1-phenotype and that had positive effect on the state of the liver [133]. Similar data were obtained on a model of acute pancreatitis in rats [134]. In pancreatitis, the accumulation of Kupffer cells with the M1 phenotype in the liver is observed.…”
Section: Potential Therapeutic Approachesmentioning
confidence: 75%